Robust dynamic community detection with applications to human brain functional networks - L.-E. Martinet (Nature Portfolio, 2020)
Understanding how brain networks evolve in time remains a challenge, with the potential for significant impact to human health and disease. Here, the authors introduce a new methodology to track dynamic functional networks that is robust to edge noise, and yields well-defined spatiotemporal communities that span forward and backwards in time.